2015
DOI: 10.1111/jcmm.12704
|View full text |Cite
|
Sign up to set email alerts
|

Changes in different parameters, lymphocyte proliferation and hematopoietic progenitor colony formation in EAE mice treated with myelin oligodendrocyte glycoprotein

Abstract: Myelin oligodendrocyte glycoprotein (MOG) is an antigen of the myelin sheath, which may trigger immune cell responses and the production of auto‐antibodies in multiple sclerosis (MS). In this study, we used MOG 35‐55‐induced experimental autoimmune encephalomyelitis (EAE), a model of human MS, to assess the production of catalytically active immunoglobulin G (IgG) antibodies or abzymes which have been shown to be present in sera of patients with several autoimmune diseases. Here, we show that IgGs from the ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
369
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 38 publications
(399 citation statements)
references
References 41 publications
12
369
0
Order By: Relevance
“…In addition, the level of lymphocyte proliferation as well as cell apoptosis in different organs including bone marrow of healthy MRL-lpr/lpr and EAE mice, at stages of their prediseases and deep pathologies were also comparable [32]. In addition, it was shown that abzymes hydrolyzing MBP are formed in the early stages of human MS, unlike in later stages of SLE, while the reverse situation was observed for abzymes with DNase activity [70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87].…”
Section: Cell Apoptosis In Sle Prone Micementioning
confidence: 86%
See 3 more Smart Citations
“…In addition, the level of lymphocyte proliferation as well as cell apoptosis in different organs including bone marrow of healthy MRL-lpr/lpr and EAE mice, at stages of their prediseases and deep pathologies were also comparable [32]. In addition, it was shown that abzymes hydrolyzing MBP are formed in the early stages of human MS, unlike in later stages of SLE, while the reverse situation was observed for abzymes with DNase activity [70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87].…”
Section: Cell Apoptosis In Sle Prone Micementioning
confidence: 86%
“…For example, using experimental C57BL/6 autoimmune encephalomyelitis (EAE) mice (a model mimicking human MS), it was recently shown that spontaneous EAE development leads to the production of Abs to myelin basic protein (MBP) and DNA and to Abzs efficiently hydrolyzing these substrates, which associated with significant changes of the differentiation profile and level of lymphocytes proliferation of mice bone marrow HSC [32]. Immunization of these mice with MOG35 results in a very strong acceleration in the development of EAE and a very strong increase of the relative activities of abzymes hydrolyzing MOG, MBP, and DNA.…”
Section: Cell Apoptosis In Sle Prone Micementioning
confidence: 99%
See 2 more Smart Citations
“…At that time, antibody titres for various anti‐antigens correspond to a range of indices typical for healthy humans and mice. A detectable level of abzymes can indicate the disease onset or pre‐disease stage, while an increase in catalytic activities follows the development of clear pathological symptoms . To understand the disease, it is therefore essential to identify all possible parallel and complementary mechanisms of MS development.…”
Section: Introductionmentioning
confidence: 99%